2013
DOI: 10.1098/rsta.2011.0586
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of electron and ion irradiation of solid acetonitrile (CH 3 CN)

Abstract: The structure and bonding of solid acetonitrile (CH₃CN) films on amorphous silica are studied, and chemical and physical processes under irradiation with 200 keV protons and 250-400 eV electrons are quantified using transmission infrared spectroscopy, reflection-absorption infrared spectroscopy and temperature-programmed desorption, with the assistance of basic computational chemistry and nuclear materials calculations. The thermal desorption profiles are found to depend strongly on the balance between CH₃CN-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
7
41
0
Order By: Relevance
“…[24][25][26] Previous laboratory studies were also dedicated in understanding the energetic processing of CH 3 CN ices under conditions that mimic those found in astrophysical environments. Similar results were achieved by Abdugalil et al 28 employing the reflection-absorption infrared spectroscopy (RAIRS) technique before and after 200 keV proton irradiation of frozen CH 3 CN deposited at 15 K. On the other hand, Abdugalil et al 28 noted that the electron irradiation in the 250-400 eV energy range leads only to CH 3 CN surface removal by electron-promoted desorption. Similar results were achieved by Abdugalil et al 28 employing the reflection-absorption infrared spectroscopy (RAIRS) technique before and after 200 keV proton irradiation of frozen CH 3 CN deposited at 15 K. On the other hand, Abdugalil et al 28 noted that the electron irradiation in the 250-400 eV energy range leads only to CH 3 CN surface removal by electron-promoted desorption.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…[24][25][26] Previous laboratory studies were also dedicated in understanding the energetic processing of CH 3 CN ices under conditions that mimic those found in astrophysical environments. Similar results were achieved by Abdugalil et al 28 employing the reflection-absorption infrared spectroscopy (RAIRS) technique before and after 200 keV proton irradiation of frozen CH 3 CN deposited at 15 K. On the other hand, Abdugalil et al 28 noted that the electron irradiation in the 250-400 eV energy range leads only to CH 3 CN surface removal by electron-promoted desorption. Similar results were achieved by Abdugalil et al 28 employing the reflection-absorption infrared spectroscopy (RAIRS) technique before and after 200 keV proton irradiation of frozen CH 3 CN deposited at 15 K. On the other hand, Abdugalil et al 28 noted that the electron irradiation in the 250-400 eV energy range leads only to CH 3 CN surface removal by electron-promoted desorption.…”
Section: Introductionsupporting
confidence: 72%
“…28 In these circumstances, similar non-thermal desorption processes, as studied here by ESID, are expected to occur during the warm-up phase of the inner envelope of pre-stellar cores prior to the hot core phase, when ice mantles are up to sublimate. The CH 3 CN ice film was grown in situ at 120 K, which is close to the thermal desorption peak of CH 3 CN at approximately 135 K under laboratory conditions.…”
Section: Introductionmentioning
confidence: 61%
“…Acetonitrile (CH 3 CN) exhibits two H À resonance features between 6 and 13 eV, with a small shoulder centered at about 8 eV and a more intense peak centered at 11 eV. While acetonitrile was amorphous at 90 K, at 130 K, it likely condenses as a crystal in an orthorhombic b-phase (Hudson and Moore, 2004) In addition, CH 3 CN ice condensed at 130 K, is near the onset for appreciable thermal desorption, with a sublimation temperature of $135 K (Abdulgalil et al, 2013). This may result in a smaller condensation coefficient and a thinner ice than expected at 90 K for the same deposition time.…”
Section: Acetonitrilementioning
confidence: 97%
“…Recent work by Abdulgalil et al (2013) investigating irradiation experiments of thin films of acetonitrile using 200 keV proton derived a secondary electron-promoted destruction of CH 3 CN of $4 Â 10 À18 cm 2 from a secondary electron flux of about 3.8 Â 10 14 cm À2 s À1 and an energy distribution ranging from a few eV to $300 eV. Accordingly, these data indicate that a significant fraction of low-energy (<20 eV) electrons will participate in CH 3 CN destruction via DEA processes.…”
Section: Dea Cross Sectionsmentioning
confidence: 99%
“…These changes can be attributed to a transition between a disordered phase to a much ordered one, i.e., an amorphous to crystalline transition. Some examples are reported by Hudgins et al (1993), Palumbo et al (1999), Moore et al (2010), Abdulgalil et al (2013), and Modica & Palumbo (2010). Bossa et al (2012) reported about the thermal processing of porous amorphous solid water.…”
Section: Introductionmentioning
confidence: 99%